Numerical Analysis on the Aerodynamic Performance of a High-speed Train Operating on Various Embankment Heights Under the Influence of Crosswinds - Ishak, Izuan Amin; Khalid, Amir; Nik Nur Amyra Adilla Noor Khairullah; Mohammad Arafat; Nurshafinaz Mohd Maruai; Fadhilah Mohd Sakri (International Journal of Integrated Engineering, 2024)
Given the unavoidable geographical surface, railings must be raised above ground level in some cases, which is known as an embankment. It was discovered that the height of the embankment had a significant influence on the slipstream on the train’s leeward side especially during crosswind conditions. The primary objectives of this study were to investigate the impact of varying embankment heights on the aerodynamic characteristics of a high-speed train under different crosswind conditions using computational fluid dynamics (CFD) analysis. The German Aerospace Center DLR’s Next-Generation High-speed Train (NG-HST) model has been used for this study. The yaw angles (?) are ranging from 10º to 50º in 10° increments. The Reynolds number based on the model’s height and freestream velocity at the computational domain is 1.3 x 106. In the results, it shows that embankment height and crosswind ? has a significant impact on the aerodynamic characteristics. Essential aerodynamic parameters that have a significant impact on train stability, such as the drag, lift, and side force coefficients, as well as the roll, yaw, and pitch moment coefficients, revealed that the higher the ?, which included 40º and 50º, produced poor results compared to the lower ?, which included 10º, 20º, and 30º. In terms of visual appearance, rising of crosswind angles have a greater impact on the formation of vortices on the leeward side of the train body and embankment. Thus, it can be concluded that the embankment heights and crosswind angles are crucial in determining train safety operations.